Photon-induced conduction modulation in SiO2 thin films embedded with Ge nanocrystals - Tan, M. C. (2010)
The authors report the photon-induced conduction modulation in SiO2 thin films embedded with germanium nanocrystals (nc-Ge). The conduction of the oxide could be switched to a higher- or lower-conductance state by a ultraviolet (UV) illumination. The conduction modulation is caused by charging and discharging in the nc-Ge due to the UV illumination. If the charging process is dominant, the oxide conductance is reduced; however, if the discharging process is dominant, the oxide conductance is increased. As the conduction can be modulated by UV illumination, it could have potential applications in silicon-based optical memory devices.